Desproporcionalidade da representaç\~ao dos estados no Congresso Nacional e seus efeitos na alocaç\~ao dos recursos federais - Mathieu Turgeon; Pedro Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper explores how malapportionment affects the way Brazilian federal government allocates its resources to subnational units. Specifically, we argue that over-represented subnational units receive more per capita in discretionary federal spending because the executive seeks its legislative support. Using data from 1997 to 2010, we propose and evaluate a model for explaining discretionary federal spending. The findings support the hypothesis that over-represented subnational units receive more than under-represented ones, presumably because the central government strategically target them to gain legislative support.
Keywords: D72; 330; malapportionment; Executive-Legislative relations; fiscal federalism; Brazil